2015
DOI: 10.1002/cncr.29649
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term visual outcome after chemotherapy for optic pathway glioma in children: Site and age are strongly predictive

Abstract: BACKGROUND: Optic pathway gliomas (OPGs) are commonly noted in pediatric oncology services. Radiotherapy is effective at controlling tumors, but has many undesirable late effects, especially in patients with neurofibromatosis. Chemotherapy is commonly used to preserve vision and delay or eliminate the need for radiotherapy. Despite visual threat being a common reason to initiate chemotherapy in patients with OPG, reports of visual outcome after chemotherapy are not common and reports of long-term visual outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 24 publications
2
37
0
7
Order By: Relevance
“…Previous studies have suggested that OPG involvement in the optic chiasm vs the optic tract carries a higher risk of vision loss. 3,5,14,[26][27][28] Despite the optic tracts demonstrating a statistically significant increased risk of vision loss compared to the optic chiasm in these studies, the positive predictive value is less than chance. 3 Our data do not support increased risk of vision loss from optic tract involvement, but instead suggest that OPG and AVP volume along with total brain volume are highly predictive of damage to the visual pathway.…”
Section: Mri Volumetric Analysis Gadolinium Contrast-enhancedmentioning
confidence: 73%
“…Previous studies have suggested that OPG involvement in the optic chiasm vs the optic tract carries a higher risk of vision loss. 3,5,14,[26][27][28] Despite the optic tracts demonstrating a statistically significant increased risk of vision loss compared to the optic chiasm in these studies, the positive predictive value is less than chance. 3 Our data do not support increased risk of vision loss from optic tract involvement, but instead suggest that OPG and AVP volume along with total brain volume are highly predictive of damage to the visual pathway.…”
Section: Mri Volumetric Analysis Gadolinium Contrast-enhancedmentioning
confidence: 73%
“…For children with NF1-associated OPGs, there are conflicting reports whether OPGs involving isolated optic nerves and or chiasm have a better clinical prognosis than gliomas that involve structures posterior to the chiasm (i.e., optic tracts/ optic radiations) although more recently several studies favor posterior pathway involvement to have poorer visual outcome. 8,32,40,[76][77][78] In the NF1-associated OPGs with posterior pathway involvement, additional hypothalamic involvement did not confer a poorer visual prognosis in a later study. 32 Sporadic OPGs with posterior involvement also show poorer visual outcomes.…”
Section: Predicting Clinical Prognosis By Magnetic Resonance Imaging mentioning
confidence: 74%
“…Radiation therapy can be used before and after surgery (9) . After treatment of ONGs Long-term side effects may occur, such as: learning disabilities, cognitive difficulties and impairments in growth (10) .…”
Section: Introductionmentioning
confidence: 99%